Determinants of Accounting Students Understanding of Riba - Wibowo, Sigit Arie; Mulantono, Dea Rizaldi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
Currently, riba is one of the hot issues that often discussed in the field of sharia accounting and accounting student education in Islamic universities, which is sharia accounting as the major concentration. This study aims empirically to examine and prove the influence of intrinsic education, extrinsic education, educational learning, family religiosity, friendship religiosity, and organizational religiosity on students Understanding of Riba. This study used the sample of Accounting students of the Muhammadiyah University of Yogyakarta. This research also used convenience sampling technique. From the 109 questionnaires, there were 100 questionnaires available for the further process. The data obtained was then processed by using multiple linear regression analysis. The results of this study indicate that all independent variables proposed in this study have a significant positive effect on the understanding of accounting students in riba.